Experimental Evaluation of an Internally Passively Pressurized Circulation Control Propeller. (3rd February 2014) - Kweder, Jonathan; Zeune, Cale H.; Geiger, Jon; Lowery, Andrew D.; Smith, James E.
Abstract : The purpose of circulation control for fixed wing aircrafts is to increase the lifting force when large lifting forces and/or slow speeds are required, such as at takeoff and landing. Wing flaps and slats are used on almost all fixed-wing aircraft. While effective in increasing lift, they do so with penalty of increasing drag, weight, and control complexity. The goal of this research was to find an alternative way of pumping pressurized air to the trailing edge slot on a UAV propeller. This design called for rerouting stagnation pressure from the frontal propeller area through the inside of the propeller blades to ejection slots on the trailing edge. This allows for the forward velocity of the aircraft to drive the pressurization of the circulation control plenum passively, without additional hardware. For this study, a Clark-Y airfoil section propeller with an overall diameter of 0.609 meters was designed and tested. The comparison of the augmented to unaugmented propeller showed a 5.12 percent increase in efficiency, which is shown to act over the entire range of flight envelopes of the aircraft and is shown to be particularly beneficial at advance ratios above 0.30, normal operating conditions of propeller-driven UAVs.